Quantum-dot-sensitized TiO2 inverse opals for photoelectrochemical hydrogen generation - Cheng, Chuanwei (2013)
A new nanoarchitecture photoelectrode design comprising CdS quantum-dot-sensitized, optically and electrically active TiO2 inverse opals is developed for photoelectrochemical water splitting. The photoelectrochemical performance shows high photocurrent density (4.84 mA cm−2 at 0 V vs. Ag/AgCl) under simulated solar-light illumination.